The Effect Of Contract Work Patterns And Wage Systems On The Performance Of Convection Employees at PT. Harmoni Sinergi Sentosa - Hengki Engli Yandri; Muji Rahayu (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine how piece-rate work patterns and wage systems contribute to employee performance levels. The subjects of this study include all production employees working under a piece-rate system at PT Harmoni Sinergi Sentosa. This research employs a quantitative approach with a descriptive design using a survey method, applying the Slovin formula and involving 111 respondents. Data were collected through questionnaires, and the research instruments were measured using a five-point Likert scale. Data analysis was conducted using SPSS through linear regression testing to determine both partial and simultaneous effects among variables. The findings from the first hypothesis testing indicate that the piece-rate work pattern has a positive but not significant effect on employee performance. Furthermore, the results of the second hypothesis testing show that the wage system has a positive and significant effect on employee performance. This implies that the fairer and more competitive the wage system implemented, the higher the level of employee work effectiveness and efficiency. Simultaneously, piece-rate work patterns and wage systems are proven to have a significant effect on employee performance. These findings confirm that the combination of result-based work systems and appropriate wage mechanisms becomes a strategic factor in improving the performance of garment employees at PT Harmoni Sinergi Sentosa..